The big book of fashion illustration : a sourcebook of contemporary illustration - Dawber, Martin (London : Batsford, 2007)
This is a visual bible for fashion illustrators and graphic designers, giving an unprecedented variety of approaches for illustrating fashion with hundreds of stunning images.
Womenswear -- Menswear -- Youth culture -- Children -- Sport -- Accessories -- Beauty.
Keywords: Fashion drawing